Enhancement of the Tolerogenic Phenotype in the Liver by ImmTOR Nanoparticles - Ilyinskii, Petr O.; Roy, Christopher J.; LePrevost, Julie; Rizzo, Gina L.; Kishimoto, Takashi Kei (Frontiers in Immunology, 2021)
ImmTOR biodegradable nanoparticles encapsulating rapamycin have been shown to induce a durable tolerogenic immune response to co-administered biologics and gene therapy vectors. Prior mechanism of action studies have demonstrated selective biodistribution of ImmTOR to the spleen and liver following intravenous (IV) administration. In the spleen, ImmTOR has been shown to induce tolerogenic dendritic cells and antigen-specific regulatory T cells and inhibit antigen-specific B cell activation. Splenectomy of mice resulted in partial but incomplete abrogation of the tolerogenic immune response induced by ImmTOR. Here we investigated the ability of ImmTOR to enhance the tolerogenic environment in the liver. All the major resident populations of liver cells, including liver sinusoidal endothelial cells (LSECs), Kupffer cells (KC), stellate cells (SC), and hepatocytes, actively took up fluorescent-labeled ImmTOR particles, which resulted in downregulation of MHC class II and co-stimulatory molecules and upregulation of the PD-L1 checkpoint molecule. The LSEC, known to play an important role in hepatic tolerance induction, emerged as a key target cell for ImmTOR. LSEC isolated from ImmTOR treated mice inhibited antigen-specific activation of ovalbumin-specific OT-II T cells. The tolerogenic environment led to a multi-pronged modulation of hepatic T cell populations, resulting in an increase in T cells with a regulatory phenotype, upregulation of PD-1 on CD4+ and CD8+ T cells, and the emergence of a large population of CD4–CD8– (double negative) T cells. ImmTOR treatment protected mice in a concanavalin A-induced model of acute hepatitis, as evidenced by reduced production of inflammatory cytokines, infiltrate of activated leukocytes, and tissue necrosis. Modulation of T cell phenotype was seen to a lesser extent after administration by empty nanoparticles, but not free rapamycin. The upregulation of PD-1, but not the appearance of double negative T cells, was inhibited by antibodies against PD-L1 or CTLA-4. These results suggest that the liver may contribute to the tolerogenic properties of ImmTOR treatment.